Phase transitions in KDP crystals with the complex organic and inorganic impurities - Strukov, B.; Shnaidshtein, I.; Grabovsky, S (Condensed Matter Physics, 2007)
In this paper we present the results of the study of dielectric and thermal properties of KDP crystals doped with different complex organic and inorganic molecules which decorate different (pyramidal or prismatic) crystal growth sectors. It is shown that the properties of stained and transparent parts of the crystal in comparison with the corresponding parts of the nominally pure crystal are different for KDP crystals grown by means of traditional (slow) and rapid growth technique. The difference of the domain contribution into dielectric constant of the polar phase and its characteristic hysteresis in pure and dyed crystals, transition temperature position, form of the specific heat anomaly are presented and analyzed. The most probable model of incorporation of the complex impurity molecules into KDP structure is proposed.